Apollo 13 - Howard, Ron, 1954-; Broyles, William; Reinert, Al.; Grazer, Brian, 1953-; Hanks, Tom.; Paxton, Bill.; Bacon, Kevin, 1958-; Sinise, Gary.; Harris, Ed, 1950-; Quinlan, Kathleen, 1954-; Schellhardt, Mary Kate, 1978-; Lloyd, Emily Ann, 1983-; et al. (Universal City, CA : Universal, 2005)
It had been less than a year since the first man walked on the Moon, but to the American public, Apollo 13 was just another "routine" space flight. That is until the words pierced the immense void of space: "Houston, we have a problem." Stranded in a crippled spacecraft 205,000 miles from Earth, astronauts Jim Lovell, Fred Haise, and Jack Swigert fight a desperate battle to survive. Meanwhile, at Mission Control, astronaut Ken Mattingly, flight director Gene Kranz, and the efforts of a heroic ground crew race against time -- and the odds -- to bring the men home.
Disc 1. Anniversary edition; (anamorphic widescreen 2.35:1) ; Lost moon: the triumph of Apollo 13, the making of Apollo 13 ; feature commentary with director Ron Howard ; feature commentary with Jim & Marilyn Lovell ; production notes ; theatrical trailer -- Disc 2. The IMAX experience version; (anamorphic widescreen 1.66:1) ; Conquering space: the moon and beyond ; Luck 13: the astronauts' story.
Originally released in 1995 as a motion picture.
Based on the book Lost moon by Jim Lovell & Jeffrey Kluger.
Director of photography, Dean Cundey ; art directors, David J. Bomba, Bruce Alan Miller ; editors, Dan Hanley, Mike Hill ; music, James Horner ; costume designer, Rita Ryack ; production designer, Michael Corenblith ; visual effects supervisor, Robert Legato.
Tom Hanks, Bill Paxton, Kevin Bacon, Gary Sinise, Ed Harris, Kathleen Quinlan, Mary Kate Schellhardt, Emily Ann Lloyd, Miko Hughes.
MPAA rating: PG; for language, peril, and emotional intensity.
DVD ; region 1 ; widescreen (2.35:1) presentation (disc one) ; IMAX presentation (disc two) ; Dolby Digital 5.1 surround, DTS 5.1 surround, dual-layer, single-sided.
Keywords: Lovell, Jim -- Drama; Haise, Fred, -- 1933- -- Drama; Swigert, John L. -- 1931-1982 -- Drama; Apollo 13 (Spacecraft) -- Drama; Space vehicle accidents -- Drama; Action and adventure films; Feature films; Film adaptations; Feature films; Action and adventure films; Video recordings for the hearing impaired; Film adaptations